2019
DOI: 10.24052/jbrmr/v13is03/art-02
|View full text |Cite
|
Sign up to set email alerts
|

The impact of demographic factors on supermarket shopping motivations in South Africa

Abstract: The changing retail environment necessitates a need to manage supermarkets effectively by understanding shopping motivations in order to attract shoppers and remain competitive. The purpose of this research was to determine the factors that motivate shoppers to visit and buy from certain branded supermarkets. In addition, to determine if there is any relationship between shoppers' demographics and shopping motivations. The survey reached 3494 shoppers online of whom 104 responded. The data were analysed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Ultimately, the goal is to deliver an "overall consumer experience." (Das Nair, 2018;Mahlangu and Makhitha, 2019;Mielmann, 2019).…”
Section: Retailing In South Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, the goal is to deliver an "overall consumer experience." (Das Nair, 2018;Mahlangu and Makhitha, 2019;Mielmann, 2019).…”
Section: Retailing In South Africamentioning
confidence: 99%
“…Supermarkets give customers access to a variety of goods in a single location, are easily accessible, have flexible trading times and provide added services such as financial, cellular products and other services. Ultimately, the goal is to deliver an “overall consumer experience.” (Das Nair, 2018; Mahlangu and Makhitha, 2019; Mielmann, 2019).…”
Section: Retailing In South Africamentioning
confidence: 99%
“…The study reveals that the physical factors including discounts, quality, local brands, display and visual appeal, social factors comprising salesmen behaviour and choice of children, and the temporal factors which involve open space should be considered in designing marketing strategy for supermarket consumers. According to Mahlangu and Makhitha (2019), customers visit supermarkets for gratification shopping, value shopping, good service and product quality, social shopping and brand hunting. Thomas and Garland (1993) declare that the presence of a written list on a shopping trip to the supermarket is tangible evidence of out of store planning by the shopper, and this pre-planning may influence both time spent in store and expenditure.…”
Section: Evolution and Adoption Of Supermarket Concept In The Retailing Contextmentioning
confidence: 99%
“…Since a severe competition has existed among the supermarket retailers, they are exploring new strategies and tools to attract and retain shoppers. Moreover, the change in retail environment necessitates the need to manage supermarkets effectively (Mahlangu & Makhitha, 2019). Accordingly, understanding the nature of customer behaviour and major shopping motives which influence to increase of supermarket patronage of grocery shoppers is crucial for the success of this business.…”
Section: Introductionmentioning
confidence: 99%
“…Communication is essential because it enables the business to determine the success or failure of marketing leafy vegetables in South Africa [31]. Eva Nkgome Mahlangu; Khathutshelo Mercy Makhitha [32] found that consumers buy merchandise at some branded supermarkets for gratification, value for money, good service, product quality, social engagement and brand hunting, and these preferences are affected by shoppers' gender, age groups and monthly income.…”
Section: Review Of Literaturementioning
confidence: 99%